Laboratory Scale Bioremediation of Petroleum Hydrocarbon – Polluted Mangrove Swamps in the Niger Delta Using Cow Dung - Dike, E. N.; Ibiene, A. A.; Orji, F. A. (Malaysian Journal of Microbiology, 2012)
Aims: The aim of the study was to carry-out laboratory–scale bioremediation of petroleum hydrocarbon polluted mangrove swamps using cow dung as source of limiting of nutrients.Methodology and Results: In a 70 days study, the cow dung treated polluted soil had its total culturable hydrocarbon utilising bacterial/fungi, heterotrophic bacterial and fungal counts increased progressively from the 28th day to the 70th day. The control set- up showed very slight increment in its microbial growth. Alkaline pH was observed in all the treatments and control during the study period. The conductivity values of cow dung decreased progressively. In the cow dung treatment option, the nitrate concentration decreased from 35.44 mg/kg to 14.28 mg/kg. Phosphate concentration of cow dung option decreased from 25.41 mg/kg to 9.31mg/kg. The control had the nitrate decreased from 8.42 mg/kg to 6.98 mg/kg. Percentage total organic carbon (% TOC) in the cow dung option decreased from 4.06% to 0.96%. Control experiment had the % TOC decreased from 3.32% to 2.99%. Studies using Gas chromatographic analyses showed that 0%, 49.88%, and 69.85% of Total petroleum hydrocarbon (TPH) were lost at zero hour, 28th day and 70th day respectively in the cow dung option. In addition, in the control experimental set-up, 0%, 7.14% and 13.42% of TPH were lost at zero hour, 28th day and 70th day respectively.Conclusion, significance and impact of study: The use of organic nutrient sources such as cow dung has shown good promises in bioremediation of crude oil impacted Mangrove Swamps in the Niger Delta. The next line of action is to transfer the technology to pilot scale study.